Dakwah Smart: Proses Dakwah sesuai dengan Aspek Psikologis Madâu - AS, Enjang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
Daâwah has psikological dimension.In aplicate, smart and not smart of daâwah is so determinated by daâi attention to psychological aspecs of madâu such comprehension, feeling, attitude, motif and behavior. Daâwah become smart, in really, constitue daâi maximum effort in controlling and develop psychological aspecs of madâu that daâwah become effective.